Responsiveness of the Patient‐Reported Outcomes Measurement Information System Global Health Short Form in Outpatients With Systemic Lupus Erythematosus. Issue 9 (31st August 2020) - Kasturi, Shanthini; Szymonifka, Jackie; Berman, Jessica R.; Kirou, Kyriakos A.; Levine, Alana B.; Sammaritano, Lisa R.; Mandl, Lisa A.
Abstract : Objective: To evaluate the longitudinal responsiveness (sensitivity to change) of the Patient‐Reported Outcomes Measurement Information System (PROMIS) Global Health Short Form (PROMIS10) in outpatients with systemic lupus erythematosus (SLE). Methods: Outpatients with SLE who were receiving care at an academic medical center completed the PROMIS10 at 2 visits that were a minimum of 1 month apart. Responsiveness of the PROMIS10 global physical and mental health domains to Patient‐Reported improvement or deterioration of health status was evaluated, as measured by standard validated instruments. Effect sizes of changes in PROMIS10 scores between visits were evaluated using Kruskal‐Wallis testing. Results: A total of 223 SLE patients enrolled and completed baseline surveys, with 186 (83.4%) completing a second set of questionnaires. The PROMIS10 demonstrated mild‐to‐moderate responsiveness to Patient‐Reported improvement (effect size 0.29) and worsening (effect sizes –0.27 and –0.54) of health status for both global physical health and global mental health. Changes in the PROMIS10 correlated poorly with changes in physician‐reported measures of disease activity. Conclusion: The PROMIS10 showed responsiveness over time to Patient‐Reported changes in SLE health status, but not physician‐assessed changes. These data suggest that the PROMIS10 can be used to efficiently measure and monitor important aspects of the SLE patient experience that are not captured by standard physician‐derived metrics. Further studies are needed to evaluate the role of the PROMIS10 in optimizing longitudinal disease management in SLE and to determine its responsiveness in other chronic health conditions.